2016
DOI: 10.1177/0022034516647034
|View full text |Cite
|
Sign up to set email alerts
|

Gene Interactions Provide Evidence for Signaling Pathways Involved in Cleft Lip/Palate in Humans

Abstract: Nonsyndromic cleft lip with or without cleft palate (NSCL/P) is a common craniofacial birth defect that has a complex etiology. Genome-wide association studies have recently identified new loci associated with NSCL/P, but these loci have not been analyzed in a Mexican Mestizo population. A complex etiology implies the presence of genetic interactions, but there is little available information regarding this in NSCL/P, and no signaling pathway has been clearly implicated in humans. Here, we analyzed the associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 42 publications
(59 reference statements)
1
14
0
1
Order By: Relevance
“…Analysis of Irf6 expression and function in mouse and chick developmental models suggests that Irf6 might play a role in tissue fusion events during palatogenesis (Knight et al, 2006; Velazquez-Aragon et al, 2016). The Wnt target p63 (also known as TP63), a key regulator of proliferation and differentiation (Truong et al, 2006), inhibits the Wnt signaling output by repressing Wnt/β-catenin responsive elements in target genes (Katoh et al, 2016).…”
Section: Crosstalk Between Wnt Signaling Cell Adhesion Molecules Andmentioning
confidence: 99%
“…Analysis of Irf6 expression and function in mouse and chick developmental models suggests that Irf6 might play a role in tissue fusion events during palatogenesis (Knight et al, 2006; Velazquez-Aragon et al, 2016). The Wnt target p63 (also known as TP63), a key regulator of proliferation and differentiation (Truong et al, 2006), inhibits the Wnt signaling output by repressing Wnt/β-catenin responsive elements in target genes (Katoh et al, 2016).…”
Section: Crosstalk Between Wnt Signaling Cell Adhesion Molecules Andmentioning
confidence: 99%
“…More recently, whole‐exome sequencing (WES) studies have confirmed the role of variants in known NSCLP genes ( IRF6 , CDH1 , CRISPLD2 , FGFR2 , and PAX7) and identified novel candidate genes ( CTNND1 , PLEKHA7 , PLEKHA5 , and ESRP2 ) (Bureau et al, ; Cox et al, ; Pengelly et al, ). Furthermore, there is increasing evidence supporting an additive role for gene–gene interactions in NSCLP, with modifier phenotypic effects (Carlson et al, ; Chiquet et al, ; Li et al, ; D. Liu et al, ; Velazquez‐Aragon et al, ; Zhou et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, gene‐gene (G × G) and gene‐environment (G × E) interactions are being increasingly used to elucidate the etiology of NSOC . For example, using a multifactorial dimensionality reduction method, Velázquez et a found evidence of a G × G interaction for BMP4‐VAX1 and a G × E ABCA4‐folic acid consumption interaction . Multifactor dimensionality reduction (MDR) is a nonparametric and model‐free approach, which was applied to assess G × G interactions for the above six SNPs.…”
Section: Introductionmentioning
confidence: 99%
“…11 For example, using a multifactorial dimensionality reduction method, Velázquez et a found evidence of a G × G interaction for BMP4-VAX1 and a G × E ABCA4-folic acid consumption interaction. 12 Multifactor dimensionality reduction (MDR) is a nonparametric and model-free approach, 13 which was applied to assess G × G interactions for the above six SNPs. The bridge PCR products were sequenced on the Illumina X-10 (Illumina Technologies Corporation, California,USA) sequencing platform, and the operation flow was carried out according to the standard SOP.…”
mentioning
confidence: 99%